2020
DOI: 10.1186/s13044-020-00082-x
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid cancer among patients with thyroid nodules in Yemen: a three-year retrospective study in a tertiary center and a specialty clinic

Abstract: Background: The prevalence of thyroid cancer is increasing worldwide. No previous data are available on the prevalence of thyroid cancer in Yemen. We performed this study to determine the prevalence of thyroid cancer among patients with thyroid nodules in Yemen. Methods: A retrospective chart review was performed for 550 patients with thyroid nodules who underwent fine needle aspiration and/or thyroid surgery at a private endocrine clinic and at an endocrine clinic in a tertiary hospital in Yemen over a 3-year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
(30 reference statements)
1
2
0
Order By: Relevance
“…evaluated thyroid disorders histopathologically and reported that multinodular goiter was the most prevalent preoperative cytology result [ 3 ]. These results are consistent with previous findings that goiter is the most pervasive thyroid condition affecting young women in their teens and twenties [ 4 ]. Iodine-deficient regions are rampant with nodular goiter; a greater proportion of multimodular goiter in our study's representative areas may imply an iodine deficit.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…evaluated thyroid disorders histopathologically and reported that multinodular goiter was the most prevalent preoperative cytology result [ 3 ]. These results are consistent with previous findings that goiter is the most pervasive thyroid condition affecting young women in their teens and twenties [ 4 ]. Iodine-deficient regions are rampant with nodular goiter; a greater proportion of multimodular goiter in our study's representative areas may imply an iodine deficit.…”
Section: Discussionsupporting
confidence: 94%
“…study [ 3 ]. Thyroid diseases affect women more than men, owing to thyroid disorders' autoimmune nature and changes in thyroid function during pregnancy [ 4 ]. The main indications for thyroid surgeries are thyroid cancer, toxic multinodular goiter, toxic adenomas, local compressive symptoms, Graves' disease that failed or refractory to medical treatment or for whom medical management may not be advised, such as those attempting to become pregnant, and, rarely, cosmesis [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…The study revealed a distinct female preponderance over males with a ratio of 10.7:1. This observation shows similarity with previous studies that in Yemen by Alhuraibi K. et al [4], Al-Sharafi B et al [6], and Al-wageeh S et al [9], who described , in their studies, that females to males ratios were of 11.6:1, 10.2:1 and 9:1 respectively. However, other research papers recognize female preponderance of thyroid disease to a much lesser extent: 1.85:1-2.31:1 [18,34].…”
Section: Discussionsupporting
confidence: 92%
“…The majoriy of the patients in the study were euthyroid (88.1%) and this is similar to what mentioned by Al-SharafiB. et al [6] in their studies (87.6%). However, in the work of Al-HuraibiK.et al [4], euthyroid patients were slightly less frequent 80%.…”
Section: Discussionsupporting
confidence: 90%
“…It occupies the eighth position in the ranking of cancers that affect women [ 1 , 2 ]. Worldwide, this neoplasm affects, on average, 3% to 5% of all female cancers and 0.6% to 1.5% of male cancers [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%